Performance Analysis of Refrigeration System with Thermal Energy Storage for Lateral Heat Sources - Sarala Ramasubramanian; Vinoth Raj Durairaj; Karpagaraj Anbalagan; Nivetha Govindaraj (Engineering Proceedings)
The global energy crisis, driven by factors such as increased demand, limited fossil fuel resources, and growing environmental concerns created an urgent need for energy-efficient solutions across all sectors. Among these, refrigeration systems, which are used extensively in both domestic and commercial settings, are responsible for a sizeable amount of global energy consumption. Finding ways to reduce energy used in the refrigeration could play a crucial role in mitigating the energy crisis. Phase Change Materials (PCMs) have emerged as a promising technology to enhance the energy efficiency of refrigeration systems. By storing and releasing energy in the form of latent heat, PCMs optimize energy conversion rate of the processes, reduce power consumption, and lower the overall environmental impact. The present research focus Calcium Chloride Hexahydrate (CCH) as the PCM which acts as an intermediary between the heat sources to achieve optimal effectiveness. To improve system performance and optimize PCM quantity, two novel system configurations were assessed in the mass proportions of 1 kg and 2 kg of PCM with water. The incorporation of PCZ enhanced the overall heat energy utilisation, recovery of waste heat, and greater system output. And actual COP of the refrigeration system was meet out with the domestic refrigerator in ranges of 1.0759 to 1.1537. The above two novel system were proved that a vital role in removal of waste latent heat into lateral use in the ranges of 110.8 kJ (min.) into 226.8 kJ (max.). Finally proposed system was avoided global warming temperature raise because of uses of waste heat into lateral uses in the refrigeration systems.